Modeling of dynamic behavior of printed circuit board (PCB) subjected to mechanical shock loading - 187305 Lau, Chin Wei; Nazri Kamsah; Fakulti Kejuruteraan Mekanikal (2006)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006